Round Robin as an Interactive Technique to Teach Speaking - Destia Herlisya; Purna Wiratno (Journal on Education, 2023)
English is a language that is loved by everyone because of its role as the language that unifies the nation. Most people in the world speak English. No wonder if everyone is competing to be able to master this language in order to communicate and absorb information from outsiders. But in fact, English is still a scourge for most students in Indonesia. Moreover, there are four English skills that the students must master, namely, reading, writing, listening and speaking. Speaking is a productive skill. For some of English learners, speaking is the main point in learning English, but on the other hand, speaking is also a very difficult skill to master. Therefore, it requires various kinds of learning methods and techniques that can improve students' speaking skills. This study aims to see the effect of the round robin technique on students' speaking skills. This technique has many positive impacts on learning speaking in the classroom. This technique also makes students more interactive and raises the confidence of students to dare to speak English in their daily lives. This research is a quantitative study conducted at STKIP PGRI Bandar Lampung. There are two classes which are used as research subjects, namely the control class and the experimental class. The experimental class received treatments from the round robin technique, while the control class used the direct method.